2009
DOI: 10.1128/aem.00944-09
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Characterization of Resistant Escherichia coli in Fecal Deposits from Cattle Fed Subtherapeutic Levels of Antimicrobials

Abstract: Model fecal deposits from cattle fed or not fed antimicrobial growth promoters were examined over 175 days in the field for growth and persistence of total Escherichia coli and numbers and proportions of ampicillinresistant (Amp r ) and tetracycline-resistant (Tet r ) E. coli. In addition, genotypic diversity and the frequency of genetic determinants encoded by Amp r and Tet r E. coli were investigated. Cattle were fed diets containing chlortetracycline (44 ppm; A44 treatment group), chlortetracycline plus sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…These drug resistant E. coli can be spread in the environment where humans and animals acquire infections resulting difficulties in treating these cases (Alexander et al, 2009). The prevalence of antibiotic resistant E. coli observed in this study appeared to be similar to several other studies Nazir et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…These drug resistant E. coli can be spread in the environment where humans and animals acquire infections resulting difficulties in treating these cases (Alexander et al, 2009). The prevalence of antibiotic resistant E. coli observed in this study appeared to be similar to several other studies Nazir et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…This quantitative study further explores the differential selection and co-selection of the resistance genes found in the fecal metagenome, based upon pen-level antimicrobial regimens. Several studies, including this study on E. coli isolates, have demonstrated the phenomenon of differential selection of resistance genes based on chlortetracycline exposure242627. Other studies have likewise reported associations among various tetracycline and ceftiofur-resistance genes28293031.…”
supporting
confidence: 54%
“…Consideration of the results of this study, the study by Daniels et al, and the mathematical modeling of the persistence of bla CMY-2 ESC r E. coli in cattle environments performed by Volkova et al (26), it is likely that both conjugal transfer and clonal expansion contribute to bla CMY-2 IncA/C plasmid persistence in commensal E. coli. We note that E. coli has been demonstrated to survive for at least 6 months in cattle fecal pats (42,43) and for at least 6 weeks on feedlot surfaces after the removal of cattle (44). Thus, we theorize that in individual feedlots, persistence of bla CMY-2 ESC r E. coli occurs primarily by a cycle of ingested and shed clonal populations "adapted" to survive the specific stresses encountered in cattle and the environment at the individual feedlot level.…”
Section: Discussionmentioning
confidence: 99%